A Sociological and Mimesis Studies on the Forms of Social Issues and Critique in Indonesian Novels - Asmawati Asmawati; Ridha Hasnul Ulya; Jasril Jasril (STAI Hubbulwathan Duri, 2023)
This study was intended to characterize and analyze the portrait of social issues in Indonesian society depicted in Indonesian literature. This descriptive qualitative study used a grand theory of the literature sociology and a mimetic approach. The research gap of this study lies in its specific focus on social themes addressed by female writers and its exploration of how literary works contribute to a broader understanding of social dynamics. Here are the steps undertaken in data collection for this research: establishing the research objectives, selecting novels that address social issues or themes, closely reading and examining the novels, making notes, identifying units of analysis, and recording relevant quotations or dialogues pertaining to social critique. The data were then examined using content analysis, which was conducted employing 5 novels as the data sources. According to the analysis's findings, poverty was the most prevalent social issue in Indonesian literature because people were accused of being political prisoners by the new order regime and hence were unable to obtain quality employment. Crime, family dysfunction, the development of modern modes, transgressions of social norms, population, environment, religious issues, and social bureaucracy issues were among the social issues of the Indonesian people that were discovered. The implications of this research lie in the endeavour to provide a novel contribution to the understanding of the relationship between literature and society. In other words, literature serves as a means to critique and reflect upon existing social issues.